Is doing good, good enough? : a study on the relationship between ESG and firm performance, financial risk, and capital structure decisions - Ribeiro, Maria Figueiredo (2024)
This study investigates the relationship between ESG - as well as its individual components - and firm performance, which is measured by return on assets and return on equity, financial risk, which is measured by credit ratings, and capital structure decisions, which are measured by the total debt over total assets ratio. To do so, this research focused on S&P500 firms during the timeframe 2006-2022. The main statistical method used was OLS but in the robustness tests section such relationships were tested using other statistical methods – OLS with lagged independent variables, SUREG and 2SLS. By doing so, an inconclusive relationship is found between ESG (as well as the social and governance components) and firm performance. However, a positive and significant relationship is identified between the environmental pillar and ROA and ROE. Regarding the relationship between ESG and higher credit ratings, a positive and significant relationship is observed across the four statistical methods considered. The results also indicate that the social and governance pillars contribute to this. Finally, when it comes to the relationship between ESG and capital structure decisions, results are again inconclusive as different methods yield different conclusions.